Pregnancy after repaired bladder exstrophy: a case report - Dineli Kalansuriya; Jay Roberts; Sumudu Britton; Rebecca Marie Kimble (Case Reports in Women's Health, 2025)
Bladder exstrophy (BE) is a rare congenital anomaly of the anterior abdominal wall which results in externalisation of the distal urogenital tract and requires multiple surgeries for repair in early childhood. Pregnancy in patients with repaired BE can be high risk and may present with complications across the entire pregnancy. The literature reports decreased fertility rates and increased rates of miscarriage, preterm birth, placental abruption and postpartum complications in pregnancy for people with repaired bladder exstrophy. The present report concerns the case of a pregnant 27-year-old primigravida patient with repaired bladder exstrophy with an extreme bicornuate uterus. She experienced cervical shortening, recurrent urinary tract infection (UTI) with emerging antibiotic resistance, pelvic girdle pain and postpartum urinary incontinence. This pregnancy was managed by a large multidisciplinary team consisting of obstetrics, urology, infectious diseases, maternal foetal medicine, obstetric medicine and allied health. She achieved a term pregnancy that was delivered by elective individualised caesarean section.